Material didáctico y su incidencia en la motricidad gruesa - Jimenez Baquerizo, Hector Efren (2022)
Many teachers think that teaching resources are unimportant but they are wrong, it is essential to properly choose teaching resources and materials because they constitute fundamental tools for the development and enrichment of the teaching-learning process of students. Recognizing that not all the materials have been designed with the didactic intentionality in the development of the learning sessions, since they awaken and develop school interest and in this way they effectively motivate learning another important point with the application of the didactic processes the student's way of studying would be achieved, generating productive and competitive students. The present investigation is constituted by theoretical concepts which fundamentally guides what are didactic materials and their incidence in the gross motor skills of different authors, books, projects, magazines, theses, which have been found regarding the study variables, the same as help clarify this investigation. The techniques applied to the collection of information will help us to discern the variables. Then you have the results of the research, which is composed of the analysis and interpretation of the results obtained with fundamental tools, to have access to the information that the study can define. For the present case study, three interviews were conducted with 5 detailed questions and surveys were conducted consisting of ten questions in which the student must mark with an x the answer they interpreted according to their personal opinion. The idea when developing the present investigative work is to initially benefit the students of the Educational Unit "José María Estrada Coello", in Babahoyo, Clemente Baquerizo Parish, being able to be projected to the other children of Los Ríos province and the country. It is based on the need to provide ways to meet the needs of children and teachers who are part of basic education and consequently the logical demands of the population.